Língua: questões ideológicas, discursivas e a identidade cultural. Qual será, realmente, o segredo? - Pavarini, Selma Rizério Betaressi (2009)
This work approaches the ideological formations in the historic and current situation, inside the The Secret O Segredo by Rhonda Byrne, the author, who induces its general context of discursive formations. The post-modern man faces the stage which he has his relation with the discourse, nevertheless, he loses references and manifestations in the disconnecting of the infinite ideological complexities and the representations of new social roles. The book explores these subject s current questions and, through the language and its perfect arrangements, intends to centralize and unify him, promising the discovery of the human centralization which is in the relation I/ you. In such a manner, the enunciators positions in the contexts, the words of place and person, the ideological and discursive formations inside the book, showing the sense s effects in the discourse, in the language and in the post-modern subject are analyzed, based in the studies of French Discourse Analysis and Cultural Identity.